Лишайники острова Зміїний (Україна) - Назарчук, Ю.С.; Кондратюк, С.Я. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
В результате исследования лихенофлоры о. Змеиный (Украина) идентифицировано 72 вида лишайников, среди которых Opegrapha demutata, O. chevallieri и Physcia tenella subsp. marina — новые для территории Украины, а также 10 видов новых для степной зоны Украины и 47 — для северо-западного Причерноморья. Анализируется систематическая структура лихенофлоры, приуроченность к типам субстрата, частота встречаемости, а также связь лихенофлоры острова с другими степными лихенофлорами. As a result of research of lichen flora of Zmiiny Island (Ukraine) 72 species of lichens are identified, among which Opegrapha demutata, O. chevallieri and Physcia tenella subsp. marina are new for territory of Ukraine, and also 10 new species for the Steppe zone of Ukraine and 47 — are new for northwestern Prychornomor'ya. The systematic structure of lichen flora, distribution of lichens on various substratum types, frequency, and also relation of lichen flora of studied island with other steppe lichen floras, are analyzed in the article.